Exploring amide linkage in a polyviologen derivative towards simultaneous voltammetric determination of Pb(II), Cu(II) and Hg(II) ions - Bhushan Gadgil; Pia Damlin; Evgenia Dmitrieva; Timo Ääritalo; Carita Kvarnström (Elseveir, 2022)
In this study, we report reductive electrosynthesis of a polyviologen derivative bearing amide linkage in its side chain, derived from a cyanopyridinium based monomer with amide functionality. The as grown film was characterized by cyclic voltammetry which displays a well-defined and reversible two step redox response characteristic of viologen. FTIR analysis show evidence of amide linkage and successful reduction of cyanopyridinium moieties to polyviologen. In situ multi ESR/UV-Vis-NIR spectroelectrochemistry show a single line in ESR signal, thereby suggesting polarons as the only charge carrier involved during charging/discharging process. Furthermore, a characteristic UV–Vis absorption spectra confirms viologen formation. Finally, the polyviologen film is subjected to simultaneous voltammetric determination of heavy metal ions, Pb(II), Cu(II) and Hg(II). The amide linkage in the polyviologen derivative is supposedly complexing these divalent metal ions, enabling their sensitive and simultaneous determination with low detection limits.